1992
DOI: 10.1093/ptj/72.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Single 30-Minute Treatment of High Voltage Pulsed Current on Edema Formation in Frog Hind Limbs

Abstract: The purpose of this study was to investigate the effect of a single treatment of high voltage pulsed current (HVPC) on edema formation. Twenty-four frogs were anesthetized, and both hind limbs of each frog were traumatized by impact. Limb volumes were measured by water displacement immediately before and after trauma and at predetermined intervals for 24.0 hours posttrauma. One limb of each frog was randomly selected to receive 30 minutes of continuous, 120-pulse per second, cathodal HVPC at voltages 10% less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…These results agree with previous animal studies 7,8,10,11,25,27 that showed the effectiveness of HVPC(-) in the treatment of posttraumatic edema.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results agree with previous animal studies 7,8,10,11,25,27 that showed the effectiveness of HVPC(-) in the treatment of posttraumatic edema.…”
Section: Discussionsupporting
confidence: 93%
“…The reduction in edema using this intensity has been shown in several animal studies 7,8,[10][11]25,27,28 . Another study used a current at motor threshold in the treatment of ankle sprain (acute phase) in humans and found no difference between the treatment group and the CG 16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations